FREQUENCY OF LUNG TUMORS IN THE PATHOLOGY DEPARTMENT OF SANATORIO ADVENTISTA DEL PLATA, SMOKING AND TYPES OF ANATOMOPATHOLOGICAL DIAGNOSES - Urbelz, Gabriel S.; Nikolaus, Yanina G.; Tiscornia, Alicia M.; Cítera, Lilia G. (European Scientific Journal, ESJ, 2014)
OBJECTIVES: To evaluate the frequency of lung cancer in the Pathology department of Sanatorio Adventista del Plata (SAP PD) Libertador San Martin, Entre Rios, Argentina during the years 1966-2010. Determine in both genders the smoking as relating it to different histological types. Verify increased adenocarcinoma. Locate the frequency of lung cancer compared to other cancers in the SAP PD. METHODS: A descriptive, retrospective study. It included 383 men and 72 women diagnosed with lung cancer, from 35 to 86 years of age, between 1966 and 2010 in the SAP PD. File Data pathology were compared with the medical records of every patient, assessing smoking. It was appealed to techniques used in immunohistochemistry. Data were processed using Excel. RESULTS: Lung cancer is prevalent in the male sex ratio of 5.3:1. Thirty six percent of male cases were squamous cell carcinoma and 54% of cases involving women were adenocarcinomas. 90% were severe smokers and 93% smoked for over 20 years. Until the decade of the 80’s squamous cell carcinoma was the most frequent in the SAP PD, however, adenocarcinoma incidence increased, reaching 40% in the last decade. Of all cancers, lung cancer, does not exceed 5%, with the most frequent being skin cancer. CONCLUSIONS: Lung cancer is more common in men smokers. Adenocarcinoma rise is observed. The incidence of lung cancer in the SAP PD decreased in the last decade).